Combination of bolus 5-fluorouracil, folinic acid and mitomycin C in advanced gastric cancer: results of a phase II trial - Hartung, Gernot; Hofheinz, Ralf-Dieter; Buchheidt, Dieter; Rost, A.; Brecht, A.; Forche, K.; Schröder, M.; Wojatschek, C.; Fritze, D.; Hehlmann, Rüdiger; Queißer, Wolfgang (Onkologie, 2000)
Background: Gastric carcinoma still is a worldwide major cause of cancer death. Although various chemotherapy schedules yielded high response rates, median survival rarely exceeds 8-10 months. Many regimens are inevitably associated with significant toxicity which jeopardizes their value as palliative treatment, especially in patients with reduced performances status. Therefore, we initiated a phase II study for the treatment of advanced gastric carcinoma using a bolus regimen with mitomycin C (MMC), 5-fluorouracil (5-FU) and folinic acid (FA), allowing the enrollment of elderly patients or those with reduced performance status (WHO grade 2). Patients and Methods: Between 1996 and 1998 we recruited a total of 58 patients with advanced gastric cancer to receive bolus MMC 3 mg/m2, 5-FU 450 mg/m2, and FA 100 mg/m2 on days 1-3. Treatment was repeated on day 22. 53 patients met the inclusion criteria: male n = 36, female n =17; median age 65 (range 26-81); mean WHO status 1 (range 0-2). Results: Out of 53 patients 50 were evaluable for response, all 58 patients who received therapy were evaluable for toxicity. Eleven patients (22%) achieved partial remission (95% CI: 11.5 -36.0%), 24 (48%) no change and 15 (30%) were progressive. Median overall survival was 11.5 months, the median time to progression 6.0 months. Out of 290 treatment cycles the worst toxicities observed (WHO 2/3/4) were as follows: anemia 13/3/1, leukopenia 19/1/1, thrombopenia 11/3/0, nausea/emesis 11/2/0, infections 2/1/0, diarrhea 14/2/0, and stomatitis 6/1/1. One patient developed hemolytic-uremic syndrome. Conclusions: The tumor control rate (PR + NC) of 70% was comparable to established chemotherapy regimens, while median overall survival was promising. Toxicity was mild, allowing the treatment especially for elderly patients and on outpatient basis.
Gesehen am 19.05.2022